MODEL FOR EVALUATING THE EFFECTIVENESS OF EXTERNAL MUNICIPAL FINANCIAL CONTROL BODIES - Pashkova T. A.; Geraschenko I. P.; Seitakhmetova N. L. (Scientific Journal of Pedagogy and Economics, 2021)
. External municipal financial control bodies based on the existing models of the evaluating the effectiveness of their activities. The authors of this article have developed the model of the effectiveness of the external municipal financial control bodies, composed of complex criteria for control and expert-analytical activities, including the system of indicators for comprehensive assessment of performance, efficiency, intensity and dynamism of the activities of external municipal financial control bodies. The features of the activities of the external municipal financial control bodies of the different subjects of the Russian Federation, their powers, scale and differences in the level of economic development, quantitative results of the activities, the quality of external municipal financial control, as well as scientific approaches of Russian and foreign authors were taken into account. In order to exclude the impact on the comprehensive assessment of the effectiveness of the external municipal financial control bodies of the dimension of indicators, the method was chosen for normalizing the values of indicators relative to the highest and lowest values, with the conversion of the values of indicators to the point scale in the range from 1 to 10. The convolution of point values of indicators into the complex criterion is carried out on the basis of normalization of the sum of actual point values relative to the sum of the maximum possible point value of the indicator. On the basis of complex criteria, generalized criterion for the effectiveness of the external municipal financial control bodies is determined; it is calculated as the geometric weighted average of complex criteria. For the purpose of analyzing the effectiveness of the external municipal financial control bodies, the discriminant function divides them into more or less effective ones